Producción, comercialización y rentabilidad del banano (musa paradisiaca-cavendish) y su relación con la economía del cantón La Maná, año 2011 - Olvera Resabala, Evelin Lisseth (2012)
During the present investigation about the production, trade and prices of bananas (Musa Paradise-Cavendish) and its relationship with the economy of La Maná canton, Cotopaxi Province; it was found a very extensive theoretical base such as costs of production.In addition, variables of the macro and microeconomics are presented which allow getting a better understanding of the marketing and export of bananas. In the same way, the collection of data was important. The instrument was a census that was applied to all producers in the area (80) to familiarize with the respective process and information for carrying out the theme. It permitted to consider many alternatives of questions which facilitated the investigation....